Attitude Is Everything: Examining Acceptance of Violence Items for Differential Item Functioning Across Heterosexual and Sexual Minority Youth - McMillan, Iris F. (Journal of interpersonal violence, 2024)
Acceptance of dating violence (ADV) is a cognitive risk factor for violence perpetration and a common target of prevention programs. However, frequently used items assessing ADV are characterized by heteronormative item wording, and limited research has evaluated the degree to which ADV items function equivalently for both heterosexual and sexual minority youth (SMY). The current study sought to determine if there are differences in the way heterosexual and SMY respond to ADV survey items. Secondary data from a total of 2,014 adolescents (Mage = 16.78) were used to examine differences in ADV. Results of differential item functioning analysis indicated nonuniform differential item functioning for two of eight ADV items, with heterosexual youth being more likely to express strong levels of agreements with (a) female-perpetrated physical violence in response to male-perpetrated violence and (b) female-perpetrated violence against males broadly, relative to SMY. Although these differences were of negligible magnitude and only resulted in minimal differences in overall expected average scores, heterosexual youth were more likely to strongly accept female-perpetrated dating violence compared to SMY. Findings highlight differences in ADV item response patterns across heterosexual and sexual minority identifying youth and provide preliminary evidence for group differences in acceptance of female-perpetrated dating violence. Implications for prevention programming based on current findings include greater focus on measure adaptation and development as well as more consensus on the necessity of preventing female-perpetrated violence.